Assessment of changes in the land use structure in Tra Vinh province under the scenarios of climate change and sea level rise / Tran Ha Phuong, Hoang Phi Phung, Nguyen Thanh Hung..[va nhung nguoi khac] - Tran, Ha Phuong
Currently in the context of climate change droughts salinity intrusion, sea level rise etc and through the reality, ít can be seen that the structure of land use in Tra Vinh province Viet Nam has been impacted quite strongly